Adulteration of proprietary Chinese medicines and health products with undeclared drugs: experience of a tertiary toxicology laboratory in Hong Kong. (4th October 2017) - Ching, Chor Kwan; Chen, Sammy Pak Lam; Lee, Hencher Han Chih; Lam, Ying Hoo; Ng, Sau Wah; Chen, Mo Lung; Tang, Magdalene Huen Yin; Chan, Suzanne Suk San; Ng, Candy Wai Yan; Cheung, Jana Wing Lan; Chan, Tina Yee Ching; Lau, Nike Kwai Cheung; et al.
Abstract : Aims: Proprietary Chinese medicines (pCMs) and health products, generally believed to be natural and safe, are gaining popularity worldwide. However, the safety of pCMs and health products has been severely compromised by the practice of adulteration. The current study aimed to examine the problem of adulteration of pCMs and health products in Hong Kong. Methods: The present study was conducted in a tertiary referral clinical toxicology laboratory in Hong Kong. All cases involving the use of pCMs or health products, which were subsequently confirmed to contain undeclared adulterants, from 2005 to 2015 were reviewed retrospectively. Results: A total of 404 cases involving the use of 487 adulterated pCMs or health products with a total of 1234 adulterants were identified. The adulterants consisted of approved drugs, banned drugs, drug analogues and animal thyroid tissue. The six most common categories of adulterants detected were nonsteroidal anti‐inflammatory drugs (17.7%), anorectics (15.3%), corticosteroids (13.8%), diuretics and laxatives (11.4%), oral antidiabetic agents (10.0%) and erectile dysfunction drugs (6.0%). Sibutramine was the most common adulterant ( n = 155). The reported sources of these illicit products included over‐the‐counter drug stores, the internet and Chinese medicine practitioners . A significant proportion of patients (65.1%) had adverse effects attributable to these illicit products, including 14 severe and two fatal cases. Psychosis, iatrogenic Cushing syndrome and hypoglycaemia were the three most frequently encountered adverse effects. Conclusions: Adulteration of pCMs and health products with undeclared drugs poses severe health hazards. Public education and effective regulatory measures are essential to address the problem.